Amlodipine Increases Vitamin D Levels More Than Valsartan in Newly Diagnosed Hypertensive Patients: Pointing to an Additional Effect on Bone Metabolism or a Novel Marker of Inflammation?. (June 2013) - Ay, Seyit Ahmet; Karaman, Murat; Cakar, Mustafa; Balta, Sevket; Arslan, Erol; Bulucu, Fatih; Demirbas, Seref; Celik, Turgay; Naharci, Mehmet Ilkin; Demirkol, Sait; Kurt, Omer; Bozoglu, Ergun
<x xml:space="preserve">Abstract</x> Hypertension is a major challenge for public health. Appropriate antihypertensive treatment seem to provide a better life with lower morbidity and mortality rates. Another pathologic condition, osteoporosis, mainly affects postmenouposal women, and constitutes a growing body of risks after a particular age. As bone is a dynamic organ system that is directly related to calcium and phosphor metabolism, imbalance in these two parameters upon aging or menopause finally may lead to osteoporosis. Today, both osteoporosis and high blood pressure are major morbidities, especially in the elderly population. There are some intriguing results on the effects of antihypertensive agents on bone metabolism in the literature. In this study, we aimed to investigate the effects of widely used antihypertensive agents, valsartan and amlodipine on vitamin D levels in newly diagnosed hypertensive population. We found that amlodipine increased vitamin D levels significantly in patients with a newly diagnosed hypertension on a 12-week treatment duration compared to valsartan.